TEORI BAYANI DALAM PENDIDIKAN DAN PENGEMBANGNNYA DALAM PENDIDIKAN AGAMA ISLAM - Musyarofah, Dyah (Al-Wihdah: Jurnal Pendidikan Islam, 2024)
The writing of this paper aims to provide a treasure of knowledge about bayani theory in education and its development in Islamic Education. To obtain data that is in accordance with the topic of discussion, the author uses library research, which is a method of obtaining data from books that are relevant to the discussion in this paper. From the results of the search for books related to the title of this paper, it can be concluded that the essence of learning design includes four components (students, goals, methods, and evaluation) and topic analysis. The four components are influenced by learning and learning theories, while topic analysis is a learning design generated from a particular discipline.